Aligning Total Quality Management, Continuous Improvement for Process Performance: An Empirical Review - Kelechi Ugwu (Journal Research of Social Science, Economics, and Management, 2023)
Purpose: The fundamental goal of this research is to develop a conceptual framework for performance, continuous process improvement, and total quality management. Design/Methodology/Approach: Exploring the literature on total quality management and other variables in connection to various relationships has been the subject of recent investigations. Findings: This paper provides an introduction of total quality management, explains how it transforms into a sophisticated strategy employed in modern businesses, and discusses the literature-based research that has been done in this field. This study suggests that total quality management, a concept popularized by Deming, be investigated in a range of industries in order to enhance product quality, reduce waste, and increase productivity. Research Restrictions/Implications: This study is an integrative evaluation of the prior research on the idea of overall quality management and its connection. Future researchers are urged to make use of descriptive survey and empirical technique to generalize its findings. Originality/Value: To reflect comprehensive quality management, continuous improvement, and process performance, this study created a conceptual framework and model. The author created a summary table to display earlier research on the subject, including authors, topics, countries, methodologies, and findings. In light of the aforementioned, the researcher filled a knowledge gap.